Socio-Technical Innovation Bundles for Agri-Food Systems Transformation - Barrett, Christopher B. (Sustainable Development Goals Series, 2022)
This open access book is the result of an expert panel convened by the Cornell Atkinson Center for Sustainability and Nature Sustainability. The panel tackled the seventeen UN Sustainable Development Goals (SDGs) for 2030 head-on, with respect to the global systems that produce and distribute food. The panel's rigorous synthesis and analysis of existing research leads compellingly to multiple actionable recommendations that, if adopted, would simultaneously lead to healthy and nutritious diets, equitable and inclusive value chains, resilience to shocks and stressors, and climate and environmental sustainability.